Digital Da’wah Strategies for Moderate Islamic Communication: A Content Analysis of Muhammadiyah East Java’s Online Platforms - Anto, Muhammad Andrey; Huda, Sholihul; Anam, Khoirul (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
This study examines how Muhammadiyah East Java advances progressive, moderate Islamic communication through three official portals, PWMU.co, Klikmu.co, and Majelistabligh.id. We conducted a qualitative content analysis of twelve purposively selected articles published between January 2022 and July 2024, complemented by three semi-structured interviews with editorial staff. The Mediatization of Religion framework provided a lens to trace adaptations to digital media logics, while Uses and Gratifications served as an interpretive lens rather than a formal coding dimension. A codebook defined three categories: (1) Moderation and Wasathiyah, (2) Progressive Islam and Muhammadiyah ideology, and (3) Religion–Science integration. Articles were coded by a primary researcher, with a limited secondary check on a subset; no formal inter-rater reliability was conducted. Findings indicate a preliminary pattern in the use of moderation and progressive frames across platforms, with PWMU.co emphasizing analytical organizational discourse, Klikmu.co prioritizing concise, shareable pieces, and Majelistabligh.id focusing on moderation and deradicalization materials. Religion–Science integration appeared less frequently. Editorial testimonies suggest perceived audience interest in moderation-oriented content, although these indicators were self-reported rather than analytics-based. The study offers preliminary evidence of coordinated platform differentiation that maintains ideological coherence within a regional Islamic organization. Limitations include small sample size, confirmatory sampling, and restricted reliability testing, which constrain generalizability and underscore the need for larger comparative studies that incorporate audience analytics.